Provincial Evidence: Long-Run Impact of Human Development Indicators on Poverty Gap and Severity - Ringga, Edi Saputra (Grimsa Journal of Business and Economics Studies, 2024)
This study aims to fill the identified gap by examining the long-run impact of human development indicators on the poverty gap and severity index in Aceh Province, Indonesia. Utilizing data from the period 2010-2022 and various methodologies such as Fully-Modified OLS (FMOLS), Dynamic OLS (DOLS), and Canonical Cointegration Regressions (CCR), the econometric results indicate that three out of four human development indicators—spending per capita, expected years of schooling, and mean years of schooling—significantly impact poverty gap and severity. However, it was found that the relationships are positive, which means that an increase in human development level worsens poverty. This empirical evidence suggests that human development indicators in Aceh Province have yet to be optimized for successful poverty alleviation. Therefore, policy recommendations for policymakers should focus on bolstering education accessibility, promoting economic empowerment initiatives, and enhancing the effectiveness of existing poverty alleviation programs in Aceh Province.